Shoulder Instability Across the Life Span - Imhoff, Andreas B.; Savoie III, Felix H. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book outlines the consensus findings of the ISAKOS Upper Extremity Committee regarding the treatment options for patients suffering from shoulder instability. The aim is to furnish readers with a precise knowledge of the presenting features of conditions typical of different ages, thereby facilitating assessment of patient characteristics and optimal treatment decision making based on the consensus of the Committee. All age groups are covered, from the very young through to the older patient. The structuring of the book essentially according to age group reflects the fact that certain forms of shoulder instability are observed at different ages. For example, while young patients tend to demonstrate instability combined with hyperlaxity, in later years, bony defects of the glenoid and humerus gain in importance. Similarly, the scope for conservative treatment varies across the life span. Each management-oriented chapter of the book includes information and guidance on anatomy, clinical examination, imaging, surgical indications and technique, rehabilitation, outcomes, and complications and their avoidance, and the text is supported by numerous high-quality illustrations.
Keywords: Medicine.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books